Defluidization of the oxygen carrier ilmenite – Laboratory experiments with potassium salts. (1st April 2018) - Zevenhoven, Maria; Sevonius, Christoffer; Salminen, Patrik; Lindberg, Daniel; Brink, Anders; Yrjas, Patrik; Hupa, Leena
Abstract: Use of biomass in combustion and subsequent CO2 capture ideally lead to negative CO2 emissions. New techniques for biomass conversion are Chemical Looping Combustion of Biomass (Bio-CLC) and Oxygen Carrier Aided Combustion (OCAC). In both techniques, the ash-forming elements of biomass, mainly consisting of potassium, calcium, sulfur, phosphorus, and chlorine, may interact with the oxygen carrier bed material, causing agglomeration and defluidization, and thus inhibit the oxidation/reduction reactions. The detailed mechanisms behind this effect are not properly understood. Ilmenite, an iron-titanium mineral, is used as an oxygen carrier in both CLC and OCAC. In this study, the interactions between ilmenite and potassium compounds, typical for biomass ashes, were studied. Mixtures of ilmenite with different potassium compounds were thermally treated in a crucible in an oxidizing environment at 850 and 950 °C. These conditions are relevant for OCAC and in the parts of CLC where oxidation of the oxygen carrier takes place. The interactions between potassium compounds, KCl, KH2 PO4, K2 CO3 and K2 SO4 and the carrier material, were studied using DTA-TGA, XRD, and SEM-EDS. Thermodynamic equilibrium calculations were carried out to verify the reactions. Results from the crucible tests were used to explain the behavior of ilmenite in the presence of potassium salts in a lab-scale fluidized bed conversion. The bed agglomeration mechanisms depend on the potassium salt: KCl glued the particles together, whereas K2 CO3 reacted with the bed particles. KH2 PO4 reacted with the bed material and glued the particles together. K2 SO4 remained non-reactive and did not influence the agglomeration of ilmenite bed particles. Highlights: Ash-forming elements of biomass, interact with ilmenite, an oxygen carrier. The bed agglomeration mechanisms depend on the ash compound present. KCl and KH2 PO4 glue the particles together, and KH2 PO4 may react with ilmenite. K2 CO3 reacts with the bed particles. K2 SO4 remains non-reactive and does not influence the agglomeration of ilmenite.